Integration of Flywheel Energy Storage Systems in Low Voltage Distribution Grids - Karrari, Shahab (KIT Scientific Publishing, 2023)
A Flywheel Energy Storage System (FESS) can rapidly inject or absorb high amounts of active power in order to support the grid, following abrupt changes in the generation or in the demand, with no concern over its lifetime. The work presented in this book studies the grid integration of a high-speed FESS in low voltage distribution grids from several perspectives, including optimal allocation, sizing, modeling, real-time simulation, and Power Hardware-in-the-Loop testing.